Defining the expression of marker genes in equine mesenchymal stromal cells - Deborah J Guest (Dove Medical Press, 2008)
Deborah J Guest1, Jennifer C Ousey1, Matthew RW Smith21Animal Health Trust, Lanwades Park, Kentford, Newmarket, Suffolk, CB8 7UU; 2Reynolds House Referrals, Greenwood Ellis and Partners, 166 High Street, Newmarket, Suffolk, CB8 9WS, UKAbstract: Mesenchymal stromal (MS) cells have been derived from multiple sources in the horse including bone marrow, adipose tissue and umbilical cord blood. To date these cells have been investigated for their differentiation potential and are currently being used to treat damage to horse musculoskeletal tissues. However, no work has been done in horse MS cells to examine the expression profile of proteins and cell surface antigens that are expressed in human MS cells. The identification of such profiles in the horse will allow the comparison of putative MS cells isolated from different laboratories and different tissues. At present it is difficult to ascertain whether equivalent cells are being used in different reports. Here, we report on the expression of a range of markers used to define human MS cells. Using immunocytochemistry we show that horse MS cells homogenously express collagens, alkaline phosphatase activity, CD44, CD90 and CD29. In contrast, CD14, CD79α and the embryonic stem cell markers Oct-4, SSEA (stage specific embryonic antigen) -1, -3, -4, TRA (tumor rejection antigen) -1–60 and -1–81 are not expressed. The MS cells also express MHC class I antigens but do not express class II antigens, although they are inducible by treatment with interferon gamma (IFN-γ).Keywords: mesenchymal stem cells, equine, gene expression